1995
DOI: 10.1038/ng0295-173
|View full text |Cite
|
Sign up to set email alerts
|

Identical mutations in the FGFR2 gene cause both Pfeiffer and Crouzon syndrome phenotypes

Abstract: Mutations in the fibroblast growth factor receptor 2 (FGFR2) gene have been identified in Crouzon syndrome, an autosomal dominant condition causing premature fusion of the cranial sutures (craniosynostosis). A mutation in FGFR1 has been established in several families with Pfeiffer syndrome, where craniosynostosis is associated with specific digital abnormalities. We now report point mutations in FGFR2 in seven sporadic Pfeiffer syndrome patients. Six of the seven Pfeiffer syndrome patients share two missense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
234
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 436 publications
(242 citation statements)
references
References 14 publications
5
234
0
3
Order By: Relevance
“…1) of the FGFR2 gene was detected (10,13) in exon IIIc of the gene. This mutation will lead to phenylalanine to serine at amino acid 354 of the FGFR2 gene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1) of the FGFR2 gene was detected (10,13) in exon IIIc of the gene. This mutation will lead to phenylalanine to serine at amino acid 354 of the FGFR2 gene.…”
Section: Resultsmentioning
confidence: 99%
“…To date, most of the patients diagnosed with Crouzon syndrome have been shown to carry mutations of the FGFR2 gene (10,15). However, mutations remain to be identified in 50-73% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other dominantly inherited human skeletal disorders are also associated with mutations in FGF receptors. Different mutations in FGFR2 are responsible for the malformations observed in patients with Crouzon and Jackson-Weiss syndromes (Jabs et al, 1994), and mutations in FGFR1 were identified as the cause of Pfeiffer's syndrome (Muenke et al, 1994), although FGFR2 mutations have also been described in sporadic Pfeiffer Syndrome patients (Rutland et al, 1995). In all three syndromes, premature closure of the skull sutures results in craniosynostosis, which in the latter two syndromes is accompanied by limb defects.…”
Section: B Fibroblast Growth Factors and Theirmentioning
confidence: 99%